Treatment of Whiplash-Associated Disorders - Part II: Medical and Surgical Interventions - Anne Conlin; Sanjit Bhogal; Keith Sequeira; Robert Teasell (Pain Research and Management)
BACKGROUND: Whiplash-associated disorder (WAD) is a term used to describe injury due to an acceleration-deceleration mechanism at the neck. In 1995, the Quebec Task Force published a report that contained evidence-based recommendations regarding the treatment of WAD based on studies completed before 1993 and consensus-based recommendations.